49=9y-68

Simple and best practice solution for 49=9y-68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49=9y-68 equation:


49=9y-68

We simplify the equation to the form, which is simple to understand
49=9y-68

We move all terms containing y to the left and all other terms to the right.
-9y=-68-49

We simplify left and right side of the equation.
-9y=-117

We divide both sides of the equation by -09 to get y.
y=13

See similar equations:

| 6xy=3x^2 | | y=-3(3)+8 | | 6x+42=2x-2 | | 2y-3+5y=y+15 | | 3x+6y=45 | | 2,295=-74t | | 7y+8(y+6)= | | 3*x+6=5*x | | 8c-4=2-4c | | (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) | | 5(5t-2)=-36 | | 9x+1=46 | | -4(y-3)=6y-7 | | m/6=-9 | | .5x+1.25y=.5 |

Equations solver categories